2016
DOI: 10.1007/s10714-016-2082-x
|View full text |Cite|
|
Sign up to set email alerts
|

Acoustic black holes: massless scalar field analytic solutions and analogue Hawking radiation

Abstract: We obtain the analytic solutions of the radial part of the massless Klein-Gordon equation in the spacetime of both three dimensional rotating and four dimensional canonical acoustic black holes, which are given in terms of the confluent Heun functions. From these solutions, we obtain the scalar waves near the acoustic horizon. We discuss the analogue Hawking radiation of massless scalar particles and the features of the spectrum associated with the radiation emitted by these acoustic black holes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 65 publications
(102 reference statements)
0
20
0
Order By: Relevance
“…Furthermore, the DRS method only requires the existence of a future horizon and is independent from the dynamical details of the horizon formation process. For applications of the DRS method, the reader may refer to [26,27,[51][52][53][54][55][56][57]. This method is also closely related to the near-horizon conformal property of the black hole geometry [58,59].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the DRS method only requires the existence of a future horizon and is independent from the dynamical details of the horizon formation process. For applications of the DRS method, the reader may refer to [26,27,[51][52][53][54][55][56][57]. This method is also closely related to the near-horizon conformal property of the black hole geometry [58,59].…”
Section: Introductionmentioning
confidence: 99%
“…(16). Studies of the draining bathtub model have actually concluded that the radial function in this case can be expressed in terms of Heun functions (see, e.g., [37]). It seems, however, that not much use can be made of these functions to find the relevant information to obtain the acoustic clouds.…”
mentioning
confidence: 98%
“…We can start by writing the spherically symmetric solution of incompressible fluid or the so-called canonical acoustic black hole metric found by Visser written as follows [36,42]…”
Section: Canonical Acoustic Black Holesmentioning
confidence: 99%
“…Then, it's not difficult to show that we end up with a spherically symmetric acustic metric also known as a canonical acoustic black hole as [42,43]…”
Section: Canonical Acoustic Black Holesmentioning
confidence: 99%
See 1 more Smart Citation